2016
DOI: 10.3389/fphar.2016.00387
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Impact of M-Tor Inhibitor Immunosuppressive Therapy after Liver Transplantation for Hepatocellular Carcinoma: Review of the Literature

Abstract: Background: Hepatocellular Carcinoma (HCC) represents the fifth most common malignancy and the third cancer-related cause of death worldwide. Hepatitis B (HBV) and C (HCV) viral infections and alcohol abuse are the principal etiological factors for HCC. Liver transplantation (LT) is oncologically the preferable approach to HCC, as it can remove all the intrahepatic tumor foci, and also the oncogenic cirrhotic liver. The use of mTOR inhibitors (mTORi) for immunosuppression after LT for HCC has been proposed due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
(72 reference statements)
2
7
0
2
Order By: Relevance
“…In this subanalysis, recurrence of HCC was numerically lower, although not statistically significant, in patients transplanted beyond Milan with EVR + rTAC compared with sTAC (5.9% versus 23.1%, P = 0.215). The results from this subanalysis are in line with the metaanalyses by Cholongitas et al36 and Tarantino et al37 who reported encouraging results with the use of mTORis in terms of prevention and treatment of HCC recurrence in patients undergoing liver transplantation for HCC.…”
supporting
confidence: 88%
“…In this subanalysis, recurrence of HCC was numerically lower, although not statistically significant, in patients transplanted beyond Milan with EVR + rTAC compared with sTAC (5.9% versus 23.1%, P = 0.215). The results from this subanalysis are in line with the metaanalyses by Cholongitas et al36 and Tarantino et al37 who reported encouraging results with the use of mTORis in terms of prevention and treatment of HCC recurrence in patients undergoing liver transplantation for HCC.…”
supporting
confidence: 88%
“…Use of mTOR inhibitor is encouraging in terms of oncological outcomes for patients undergoing LT for HCC, both for prevention and treatment of HCC recurrence although definitive data are still awaited . Most of the data supporting the potential benefit of mTOR inhibitor were available after 2014, and hence, its use for HCC management was rare prior to this period and their potential benefit is not captured in the current study.…”
Section: Discussionmentioning
confidence: 87%
“…Use of mTOR inhibitor is encouraging in terms of oncological outcomes for patients undergoing LT for HCC, both for prevention and treatment of HCC recurrence although definitive data are still awaited. 25 Most of the data supporting the potential benefit of mTOR inhibitor were available after 2014, and hence, its use for HCC management was rare prior to this period and their potential benefit is not captured in the current study. Additionally, everolimus was approved by FDA as immunosuppression agent in 2013, and considering patients included in the current study were from 2006 to 2012, everolimus was not used as immunosuppression in these patients prior to their HCC recurrence.…”
Section: Discussionmentioning
confidence: 88%
“…Simultaneously, studies have reported encouraging results for anti-cancer treatment with mTOR inhibitors. According to several studies, their use in immunosuppression regimens decreased the risk of recurrence and prolonged survival [ 105 109 ]. Publication of the results of a randomized, prospective, multi-center clinical study called the SILVER trial provided a more reliable assessment of the suitability of use of rapamycin derivatives in patients who underwent LTx due to HCC [ 110 ].…”
Section: Post-transplantation Risk Factorsmentioning
confidence: 99%